Design of the Electronics Subsystem for a High-Resolution Electro-Optical Payload Using Systems Engineering Approach - Mehmood, Nasir (Department of Electrical Engineering, 2023)
Satellite imagers, in contrast to commercial imagers, demand exceptional performance and operate under harsh conditions. The camera is an essential part of an Earth Observation Electro Optical (EO) payload that is designed in response to needs such as military demands, changes in world politics, inception of new technologies, operational requirements and experiments. As one of the key subsystems, the Imager Electronics Subsystem of a high-resolution EO payload plays very important role in the accomplishment of mission objectives and payload goals. Hence, these Electronics Subsystems require a special design approach optimised for their needs and meticulous characterizations of high-resolution space applications. This dissertation puts forward the argument that the system being studied is a subsystem of a larger system and that systems engineering principles can be applied to the subsystem design process also. The aim of this dissertation is to design the Imager Electronics Subsystem of a high-resolution Electro Optical Payload using a systems engineering approach to represent a logical integration and test flow using the space industry guidelines. The Imager Electronics Subsystem consists of group of elements forming the functional chain from the Image Sensors on the Focal Plane down to electrical interface to the Data Handling Unit and power interface of the satellite. This subsystem is responsible for collecting light in different spectral bands, converting this light to data of different spectral bands from image sensors for high-resolution imaging, performing operations for aligning, tagging and multiplexing along with incorporating internal and external interfaces.